Antimicrobial efficacy of Colgate Plax Cool Mint® mouthwash – in vivo studies - Szymanska Jolanta (Sciendo, 2020)
Hygienic procedures in oral cavity, both teeth brushing and using mouthwashes, have an influence on the composition and quantity of oral microflora. The aim of the work was to evaluate the impact of regular use of selected mouthwash on the titer of Lactobacillus and Streptococcus bacteria and Candida yeast-like fungi in the saliva.